Self-efficacy and its interrelation with family environment and metabolic control in Turkish adolescents with type 1 diabetes - (:unkn) unknown (My University, 2003)
Objective: To explore the relationship between self-efficacy, family environment (cohesion and organization) and metabolic control. Research design and methods: A total of 100 adolescents with diabetes were assessed on a single occasion. Eligibility criteria were an age range of 11-18 yr, diagnosis of type 1 diabetes of at least 1 yr duration, and ability to complete the questionnaire unaided. Adolescents completed self-efficacy and family environment questionnaires. Metabolic control was assessed by HbA1c. Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) Version 10.0. Independent paired t-tests and Pearson's correlation coefficient were used as test methods. Results: Boys and girls were comparable on self-efficacy, and self-efficacy scores were quite satisfactory for both boys and girls. There was a significant positive correlation between self-efficacy and family cohesion in girls, but self-efficacy was not related to the family environment (cohesion and organization) and metabolic control in the total sample. Conclusion: In the present study, there was no relationship between self-efficacy, family environment, and metabolic control in the total sample, but in girls, self-efficacy and family cohesion was positively correlated.
Keywords: Family environment; Metabolic control; Self-efficacy